Glutathione peroxidase activity is neuroprotective in models of Huntington's disease. - Mason, R.P.; Casu, M.; Butler, N.; Breda, C.; Campesan, S.; Clapp, J.; Green, E.W.; Dhulkhed, D.; Kyriacou, C.P.; Giorgini, F. (Nature Genetics, 2013)
Huntington's disease is a fatal neurodegenerative disorder caused by a CAG repeat expansion encoding a polyglutamine tract in the huntingtin (Htt) protein. Here we report a genome-wide overexpression suppressor screen in which we identified 317 ORFs that ameliorate the toxicity of a mutant Htt fragment in yeast and that have roles in diverse cellular processes, including mitochondrial import and copper metabolism. Two of these suppressors encode glutathione peroxidases (GPxs), which are conserved antioxidant enzymes that catalyze the reduction of hydrogen peroxide and lipid hydroperoxides. Using genetic and pharmacological approaches in yeast, mammalian cells and Drosophila, we found that GPx activity robustly ameliorates Huntington's disease-relevant metrics and is more protective than other antioxidant approaches tested here. Notably, we found that GPx activity, unlike many antioxidant treatments, does not inhibit autophagy, which is an important mechanism for clearing mutant Htt. Because previous clinical trials have indicated that GPx mimetics are well tolerated in humans, this study may have important implications for treating Huntington's disease.